DIFFERENCES OF LIFE SATISFACTION AMONG ACEHNESE UNIVERSITY STUDENTS IN MALAYSIA MALE AND FEMALE - Hayati, Pelita; SIM, CHE CHEW; Fitria, Ida (Psikoislamedia: Jurnal Psikologi, 2021)
International student mobility has over the past 10-15 years become an increasingly, more students from  across  the  world  are  able  to  participate  in  higher  education  abroad,  especially  those  from countries with  rapidly growing economies in Asian country  (i.e  Malaysia,  Indonesia, etc).  The  high  educational ranking  of  Malaysia    is  appealing  to  many Acehnese  students  including  to  study  in  Malaysia.  Studying  abroad  can  be  a challenge  having  to  adapt  and  adjust  oneself  to  a  whole  new  environment,  culture,  language, education system, lifestyle, and new friends. This study aims to investigate  the  levels  of  life satisfaction among Acehnese university students in Malaysia male and female. T-test analysis has performed to analyze the mean life satisfaction between male and female students. The result of this study reveals there was no significant difference in life satisfaction across gender. Further discussions are displayed in full view of this study.